A Multicenter Study of Beta-Lactamase Resistant Escherichia coli and Klebsiella pneumoniae Reveals High Level Chromosome Mediated Extended Spectrum β Lactamase Resistance in Ogun State, Nigeria - Folasoge A. Adeyankinnu; Babatunde O. Motayo; Akinniyi Akinduti; John Akinbo; Joseph I. Ogiogwa; Bukola W. Aboderin; R. A. Agunlejika (Interdisciplinary Perspectives on Infectious Diseases)
As a result of the ever increasing problem of multiresistant bacteria, we instituted a surveillance program with the aim of identifying the basic molecular properties of ESBL in our environment. About 197 isolates of Escherichia coli and Klebsiella pneumoniae were selected and tested for ESBL production and antimicrobial susceptibility. Plasmid profiles were determined and curing ability was tested. ESBL prevalence was 26.4% for all isolates tested, with E. coli having a greater proportion. There was absolute resistance to ampicilin, tetracycline, and co-trimaxole among tested isolates. There was above average susceptibility to the 2nd and 3rd generation cephalosporins. Plasmid profiles of tested isolates ranged from 9 kbp to 26 kbp with average of 14.99±2.3 kbp for E. coli and 20.98±1.8 kbp K. pneumoniae, 9.6% of ESBL positive E. coli plasmids were cured, while 3.9% of K. pneumoniae plasmids were cured after treatment. The present study shows an upsurge in ESBL acquisition by gram negative bacteria and evidence of cocirculation of varying subtypes of ESBL with both plasmid transmissible and chromosome encoded subtypes. This calls for universal surveillance and more effort towards molecular epidemiology of this public health treatment.